The role of the family doctor in the diagnosis and monitoring of patients with cognitive impairment and dementia - Alves, Rui Pereira (2010)
The aging of the population is a fact in our society. In conjunction with this process an increased prevalence of diseases common in the elderly, especially dementia, is found. The interview of the patient, family and caregivers aims to search for cognitive changes and their impact on day-to-day, as well as a research to specific etiologies. In the interview the use of clinical tests to assess the mental state of the patient and the functional consequences in their activities is mandatory. The application of diagnostic tests, as well as referral to secondary care providers should be judicious and timely so that the correct therapeutic approach can be provided. A good communication between the various stakeholders, must be kept, so that we can monitor and manage the treatment plan. A special attention to the families and caregivers is necessary, since they have a higher risk of diseases such as depression.